How mechanical forces can modulate the metal affinity and selectivity of metal binding sites in proteins. Issue 3 (7th January 2020) - Dudev, Todor; Frutos, Luis Manuel; Castaño, Obis
Abstract : The results obtained reveal that applying mechanical forces with a given strength and directionality can modulate the metal affinity and selectivity of metal binding sites in metalloproteins. Abstract : Mechanical forces play a key role in essential biological processes including cell growth, division, deformation, adhesion, migration and intra-cell interactions. The effect of mechanical forces in modulating the structure and properties of metal-occupied protein binding sites has not been fully understood. Here, by employing a combination of density functional theory (DFT) calculations and polarizable continuum model (PCM) computations applied on model metal-loaded EF-hand binding sites, we shed light on the intimate mechanism of the Mg 2+ /Ca 2+ competition impacted by the application of mechanical stimuli. Applying mechanical force with a specific directionality and magnitude may shift the balance between the competing metal cations in favor of a given contestant depending on the composition and strength of the coordinative bonds and robustness of the metal binding site. Furthermore, the calculations help to determine the range of mechanical rupture forces typical for these structures: these range from 0.4 to 1.5 nN depending on the nature of the metal and amino acid residue. This positions the strength of the Mg 2+ –O and Ca 2+ –O coordinative bonds between that of typical covalent and hydrogen bonds. The bonds between the metal cation and the charged amino acid residue rupture at higher forces (∼1.2–1.5 nN) relative to those of their metal–noncharged counterparts which dissociate at ∼0.2–0.4 nN.